Answer :
we have
[tex]y-6x-9=0[/tex]
Step [tex]1[/tex]
Clear the variable y
[tex]y-6x-9=0[/tex]
Adds [tex](6x+9)[/tex] both sides
[tex]y-6x-9+(6x+9)=0+(6x+9)[/tex]
[tex]y=(6x+9)[/tex]
Step [tex]2[/tex]
Convert in function notation
Let
[tex]f(x)=y[/tex]
[tex]f(x)=(6x+9)[/tex]
therefore
the answer is
[tex]f(x)=(6x+9)[/tex]
Solution:
There are two kind of variables when equation of a function is written
1. Independent variable
2. Dependent Variable
A variable is said to be independent , if it can select constant values by itself.
And, a variable is said to be independent, if it is dependent on other variable of the equation.
The given equation is , y-6 x -9=0
As, we have to write a function in which x is an independent variable and other variable y, will work as a dependent variable.
So, writing the above linear function as,
y= 6 x + 9
f(x)= 6 x + 9 →→Option (A)
Correct representation of function in which x is an independent variable and y is a dependent variable,because if we substitute different real values of x, we get different real values of y.